A device for evaluating photovoltaic (PV) module output performance and degradation - Mohd Shawal, Jadin; Athirah, Surimin; Norizam, Sulaiman; Airul Sharizli, Abdullah; Fairuz Rizal, Mohamad Rashidi (Springer Science and Business Media Deutschland GmbH, 2022)
This paper aims to design and develop a system that can extract the PV module Standard Test Condition (STC) parameters of a PV module under real operating conditions (ROC) using Arduino Board Technology. The system captures the voltage and current under ROC and by applying reverse calculation to get the STC parameters. Then the power degradation of the PV module is calculated by comparing the calculated power at STC with the actual power stated in the data specification. Based on experimental results showed that the developed system was able to identify the power degradation almost equal to the actual power degradation. 5.04% of the power degradation was obtained from the tested PV module.